2012
DOI: 10.1021/ol300570f
|View full text |Cite
|
Sign up to set email alerts
|

The Regioselective Switch for Amino-NHC Mediated C–H Activation of Benzimidazole via Ni–Al Synergistic Catalysis

Abstract: We have disclosed a new mode of a chemically regioselective switch for C-H bond functionalization of benzimidazole derivatives via a cooperative effect invoked by Ni-Al bimetallic catalysis to create a steric requirement for obtaining the linear product of styrene insertion. Yet, excluding the AlMe(3) cocatalyst switches the reaction toward branch selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Furthermore, the identity of 3 was confirmed by a single‐crystal X‐ray study, which revealed that AlMe 3 was datively coordinated to the benzimidazole nitrogen (Figure 2). 7a, 8 Thus, we postulated that coordination of the Lewis acid to benzimidazole would increase the acidity of the C2H bond, resulting in the observed higher activity. It is imperative to mention the recent advances in the use of Lewis acid additives to enhance reaction rates; for example, the groups of Hartwig, Nolan, and Knochel have employed the Lewis acids AlCl 3 and BEt 3 for reductive elimination reactions mediated by palladium 3…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the identity of 3 was confirmed by a single‐crystal X‐ray study, which revealed that AlMe 3 was datively coordinated to the benzimidazole nitrogen (Figure 2). 7a, 8 Thus, we postulated that coordination of the Lewis acid to benzimidazole would increase the acidity of the C2H bond, resulting in the observed higher activity. It is imperative to mention the recent advances in the use of Lewis acid additives to enhance reaction rates; for example, the groups of Hartwig, Nolan, and Knochel have employed the Lewis acids AlCl 3 and BEt 3 for reductive elimination reactions mediated by palladium 3…”
Section: Resultsmentioning
confidence: 95%
“…Our group has previously reported the direct amino‐NHC nickel‐catalyzed hydroheteroarylation of styrene with benzimidazole by CH bond activation, as summarized in Table 1 7a. High selectivity in favor of the branched product with good yield was observed with various styrene substrates.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Thepioneering studies on the transition-metal-catalyzed alkene hydroarylation by Murai and co-workers have described high linear selectivity in the reaction with terminal alkenes. [1b] Recently,b ranchselective hydroarylation [2] has also emerged for vinylarenes, [3] vinyl ethers, [4] and simple alkenes. [5] Although the regiocontrolled hydroarylation reactions of terminal alkenes leading to chiral molecules have been developed, the use of ac hiral catalyst for this asymmetric transformation remains to be studied.…”
mentioning
confidence: 99%
“…Rhodium(I)-catalyzed linear C-2 alkylation was reported first by Bergman and Ellman [20]. In 2012, Shih et al reported alkylations with full Catalytic Intermolecular Functionalization of Benzimidazoles DOI: http://dx.doi.org/10.5772/intechopen.87068 control of linear versus branched selectivity using AlMe 3 as a chemical switch (Figure 10) [21]. In the presence of 10 mol% of Ni(cod) 2 (cod = cyclooctadiene) and the bidentate N-heterocyclic carbene (NHC) ligand 24 in toluene, the reaction between N-methylbenzimidazole and substituted styrenes 25 afforded exclusively branched alkylation products 26 in 50-98% yields.…”
Section: Alkylationmentioning
confidence: 99%
“…The branched product is electronically favored, but the linear product arises in the presence of AlMe 3 because the benzimidazole nitrogen at position 3 will generate a Lewis acid/base adduct causing a steric switch in the preferred binding orientation of the styrene during the catalytic cycle. Thus, the linear product is formed predominantly [21].…”
Section: Alkylationmentioning
confidence: 99%